The Uzbekistan-2030 Strategy: Priority Directions And Practical Significance Of The Development Of New Uzbekistan (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the principal directions of the Uzbekistan-2030 Strategy – its orientation toward human dignity and the interests of the people, and its coverage of the questions of education and science, youth policy, economic development, public administration, and spirituality. The methodological significance of the strategy for educators in higher-education institutions, and the possibilities of linking it with the teaching process and scholarly research, are elucidated. The article also puts forward practical proposals for promoting the content of the strategy more widely.
Keywords: Uzbekistan-2030 Strategy; New Uzbekistan; human dignity; education reform; youth policy; economic development; public administration; spirituality; higher education; civil society